An Update on in Vivo Imaging of Extracellular Vesicles as Drug Delivery Vehicles - Gangadaran, Prakash; Hong, Chae Moon; Ahn, Byeong-Cheol (Frontiers in Pharmacology, 2018)
Extracellular vesicles (EVs) are currently being considered as promising drug delivery vehicles. EVs are naturally occurring vesicles that exhibit many characteristics favorable to serve as drug delivery vehicles. In addition, EVs have inherent properties for treatment of cancers and other diseases. For research and clinical translation of use of EVs as drug delivery vehicles, in vivo tracking of EVs is essential. The latest molecular imaging techniques enable the tracking of EVs in living animals. However, each molecular imaging technique has its certain advantages and limitations for the in vivo imaging of EVs; therefore, understanding the molecular imaging techniques is essential to select the most appropriate imaging technology to achieve the desired imaging goal. In this review, we summarize the characteristics of EVs as drug delivery vehicles and the molecular imaging techniques used in visualizing and monitoring EVs in in vivo environments. Furthermore, we provide a perceptual vision of EVs as drug delivery vehicles and in vivo monitoring of EVs using molecular imaging technologies.